Diamond-Like Carbon Coating Applied to Automotive Engine Components - Makoto Kano (Japanese Society of Tribologists, 2014)
The application of DLC coatings in the automotive industry has increased significantly both in terms of production volume and the kinds of applications involved. However, elucidation of the fundamental evaluation and mechanism of friction and wear properties for DLC coating are still far from sufficient level. This article discusses recent topics concerning the application of DLC coatings to automotive engine components and the related research for tribological issues of DLC coating. For the application to engine components, several typical examples are described. As an advanced one, the ta-C coated piston ring which has been applied recently to both the compression ring and the oil ring of a new mass-produced inline 3-cylinder compact gasoline engine is shown. The ta-C coated piston ring can reduce engine friction substantially compared with the conventional Cr plating ring. Additionally, the a-C:H coated aluminum piston which can be accomplished by shot-peening aluminum alloy substrate with fine tungsten particles shows exellent wear resistance. For the research, three issues of the super-low friction, the evaluation of adhesion strength and wear resistance and the rolling fatigue are discussed.